Mitonuclear mismatch alters performance and reproductive success in naturally introgressed populations of a montane leaf beetle. (27th April 2020) - Rank, Nathan E.; Mardulyn, Patrick; Heidl, Sarah J.; Roberts, Kevin T.; Zavala, Nicolas A.; Smiley, John T.; Dahlhoff, Elizabeth P.
Abstract: Coordination between nuclear and mitochondrial genomes is critical to metabolic processes underlying animals' ability to adapt to local environments, yet consequences of mitonuclear interactions have rarely been investigated in populations where individuals with divergent mitochondrial and nuclear genomes naturally interbreed. Genetic variation in the leaf beetle Chrysomela aeneicollis was assessed along a latitudinal thermal gradient in California's Sierra Nevada. Variation at mitochondrial cytochrome oxidas e II ( COII ) and the nuclear gene phosphoglucose isomerase ( PGI ) shows concordance and was significantly greater along a 65 km transect than 10 other loci. STRUCTURE analyses using neutral loci identified a southern and northern subpopulation, which interbreed in the central drainage Bishop Creek. COII and PGI were used as indicators of mitochondrial and nuclear genetic variation in field and laboratory experiments conducted on beetles from this admixed population. Fecundity, larval development rate, running speed and male mating frequency were higher for beetles with geographically "matched" than "mismatched" mitonuclear genotypes. Effects of mitonuclear mismatch were largest for individuals with northern nuclear genotypes possessing southern mitochondria and were most pronounced after heat treatment or at high elevation. These findings suggest that mitonuclear incompatibility diminishes performance and reproductive success in nature, effects that could intensify at environmental extremes.